ПЕДАГОГІЧНА СТРАТЕГІЯ ОРІЄНТУВАННЯ СТУДЕНТІВ НА ЗДОРОВИЙ СПОСІБ ЖИТТЯ (Педагогіка вищої та середньої школи, 2008)
The main aspects and point of Higher Technical Educational establishments students orienting on a healthy way of life. We also propose pedagogical strategy of students orienting on preserving and strengthening their health. In the process of Physical Training tuition we propose wide application of interactive hums and methods of training.